Effects of Rumex tianschanicus Losinsk extract on hematological indicators in experimental gastritis - Shokan, A.K.; Ginayatova, I.B.; Yergozova, D.M.; Kudrina, N.O.; Korulkin, D.Y. (KU Publ., 2021)
Gastritis is the most common gastrointestinal disease, with peptic ulcer disease accounting for 30 % of all cases, affecting about 10 % of the global population. According to 2020 statistics, 50,8 % of the population in developing countries suffers from gastritis and this number increasing annually. This study examined the medical effects of Rumex tianschanicus root extract on aspirin induced gastritis in rats. Forty five rats, 250±50 g were grouped into two: control group rats received placebo and experimental groups received acetylsalicylic acid 160 mg/kg, orally once daily for 5 consecutive days to induce acute experimental gastritis. Following gastritis registration, rats were grouped into three groups and treated with Rumex tianschanicus L. extract. The first group was given 100 mg/kg orally once a day for ten days. The second group received 50 mg/kg orally once a day for ten days. The third group did not receive the medication. At the end of the study, all the animals were Killed to determine cytological, histological changes and hematological indices. The result showed statistically significant differences (p ≤ 0,001) of total number of leukocytes, total number of erythrocytes, hemoglobin level and content of platelets but they were all within the physiological norm. As a result of the study the Rumex tianschanicus extract pharmacological properties were evaluated and its potential effect on the hematological parameters of rats during the treatment of experimental gastritis accessed. It was discovered that the Rumex tianschanicus extract has no pathological effect on peripheral blood and hemopoiesis during the period of its use. In this regard, the extract of Rumex tianschanicus is recommended for further in-depth research in experimental conditions, followed by a transition to clinical trials.
Rumex tianschanicus Losinsk сығындысының тəжірибелік гастрит кезіндегі гематологиялық көрсеткіштерге əсері
Влияние экстракта Rumex tianschanicus Losinsk на гематологические показатели при экспериментальном гастрите
Keywords: gastritis; rats; Rumex tianschanicus; hematology parameters; blood; plant extract